The A to Z of the Chinese Civil War - Leung, Pak-Wah, 1950- (A to Z guides ;, 2010)
China today remains a divided country, as a result of the Civil War between the Chinese Nationalists and Communists. The Chinese Civil War, has been regarded by many as an important subject in the study of modern Chinese history, as this protracted struggle ultimately led to the Communist victory on the Mainland and the Nationalist government's retreat to the island of Taiwan in 1949. Considered an extremely important turning point in modern Chinese history, the Civil War is also of great international significance.